Digital visibility and competitive edge: Analyzing the impact of territorial marketing on regional competitiveness - Nemyrovska, Oksana; Ievseitseva, Olena (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This study explores the relationship between territorial marketing and branding and a country’s regional competitiveness and aims to assess the impact of marketing strategies and policies of cities and territories on that regional competitiveness. Two hypotheses are examined. The first hypothesis suggests that improving a city’s visibility on the Internet attracts tourists and foreign investors. The second hypothesis highlights the importance of high-quality information content on city websites to enhance competitiveness. The study conducts a comprehensive analysis of European countries to evaluate the impact of territorial marketing on competitiveness. This includes correlation analysis of competitiveness indices, analysis of Google Trends search queries to identify city name search trends, and content analysis of city websites to assess marketing quality. The findings reveal that cities with rich historical and cultural attractions are gaining popularity online, consequently increasing their competitiveness in both the tourism and investment sectors.